From Poachers to Protectors: Engaging Local Communities in Solutions to Illegal Wildlife Trade. Issue 3 (26th September 2016) - Cooney, Rosie; Roe, Dilys; Dublin, Holly; Phelps, Jacob; Wilkie, David; Keane, Aidan; Travers, Henry; Skinner, Diane; Challender, Daniel W. S.; Allan, James R.; Biggs, Duan
Abstract: Combating the surge of illegal wildlife trade (IWT) devastating wildlife populations is an urgent global priority for conservation. There are increasing policy commitments to take action at the local community level as part of effective responses. However, there is scarce evidence that in practice such interventions are being pursued and there is scant understanding regarding how they can help. Here we set out a conceptual framework to guide efforts to effectively combat IWT through actions at community level. This framework is based on articulating the net costs and benefits involved in supporting conservation versus supporting IWT, and how these incentives are shaped by anti‐IWT interventions. Using this framework highlights the limitations of an exclusive focus on "top‐down, " enforcement‐led responses to IWT. These responses can distract from a range of other approaches that shift incentives for local people toward supporting conservation rather than IWT, as well as in some cases actually decrease the net incentives in favor of wildlife conservation.